2005
DOI: 10.2169/internalmedicine.44.1039
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Heart-Type Fatty Acid-Binding Protein Levels and the Risk of Death in Patients with Serious Condition on Arrival at the Emergency Department

Abstract: Objective Although heart-type fatty acid-binding protein (H-FABP) is a cardiac marker useful for early diagnosis of acute myocardial infarction (AMI), few data are available on its prognostic value. The objective of this study is to clarify the prognostic value of H-FABP in patients with a serious condition. Methods and PatientsWe conducted a prospective study of 617 patients who presented to the emergency department with a serious condition. The H-FABP levels on arrival at the emergency department were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Indeed, Cardiac Troponin I (cTnI) strongly predicts mortality and/or length of hospital stay such as in the case of trauma [ 17 ], sepsis [ 18 ], pneumonia [ 19 ] and COVID-19, [ 20 ] although, cTnI should be considered more as a specific marker / “gold standard” for the diagnosis of AMI [ 21 ]. Likewise, other CBs such as Cardiac Troponin T (cTnT) [ 22 , 23 ], B-type natriuretic peptide (BNP) [ 24 ], N-terminal (NT)-pro hormone BNP (NT-proBNP) [ 25 , 26 ], soluble suppression of tumourigenicity 2 (sST2) [ 27 , 28 ] and Heart-type Fatty Acid-Binding Protein (H-FABP) [ 29 ], have all been shown to demonstrate some degree of prognostic value in critically ill subgroups. This could be extremely useful for daily practice on the ICU since early measurement of specific CBs may help clinicians to identify early risk of deterioration and may allow for optimisation of ICU resources.…”
Section: Importance Of Rapid Testing For Cardiac Markers In Criticall...mentioning
confidence: 99%
“…Indeed, Cardiac Troponin I (cTnI) strongly predicts mortality and/or length of hospital stay such as in the case of trauma [ 17 ], sepsis [ 18 ], pneumonia [ 19 ] and COVID-19, [ 20 ] although, cTnI should be considered more as a specific marker / “gold standard” for the diagnosis of AMI [ 21 ]. Likewise, other CBs such as Cardiac Troponin T (cTnT) [ 22 , 23 ], B-type natriuretic peptide (BNP) [ 24 ], N-terminal (NT)-pro hormone BNP (NT-proBNP) [ 25 , 26 ], soluble suppression of tumourigenicity 2 (sST2) [ 27 , 28 ] and Heart-type Fatty Acid-Binding Protein (H-FABP) [ 29 ], have all been shown to demonstrate some degree of prognostic value in critically ill subgroups. This could be extremely useful for daily practice on the ICU since early measurement of specific CBs may help clinicians to identify early risk of deterioration and may allow for optimisation of ICU resources.…”
Section: Importance Of Rapid Testing For Cardiac Markers In Criticall...mentioning
confidence: 99%
“…Recently, it has been proposed that the de- Lately, several studies reported that heart-type fatty acid binding protein (H-FABP), a novel low molecular weight cytosolic protein, enables earlier and precise diagnosis and risk assessment in patients with acute coronary syndromes as compared to other biomarkers [7,8]. Recent data could even demonstrate an association of elevated levels of H-FABP with increased risk of death and major cardiac events in this setting, thus having important prognostic power [9].…”
Section: Introductionmentioning
confidence: 99%